PENGARUH PROSES FERMENTASI KOMBUCHA DAUN SIRSAK (Annona muricata L.) TERHADAP KADAR VITAMIN C - Ike Apriani (Biota, 2017)
Kombucha is a fermented beverage of tea and sugar with a symbiotic culture of bacteria and yeast, consumed for its beneficial effect on human health.  Kombucha contains antioxidant activity compounds.Yet, many research studies have shown that Soursop leaves contain vitamin C, Vitamin E, beta carotene, and flavoloids.  The purpose of this study was to determine the activity levels of vitamin C kombucha tea leaves of the soursop, The research was conducted in September 2016 in Chemistry Laboratory of Biology Education Study Program, Teaching Training and  Ilmu Tarbiyah Faculty UIN Raden Fatah Palembang. The research method was an experimental laboratory using a Completly Randomized Design (CRD) with 2 factors, the first factor was fermentation days (0 day (F1), 4 day (F2), 8 day (F3) and 12 day (F4)), and the second factor was the levels of soursop leaf tea is used (0 gr (K1), 20 gr (K2), 40 gr (K3), and 60 gr (K4)) with 3 replications. The results showed that there is a very real influence and interaction between fermentation days and content of soursop leaf tea is used to the levels of vitamin C. The highest levels of vitamin C present in the sample F4K4 (12 day / 60 gr) of 343.79 mg / 100 mL, and lowest vitamin C levels in samples F4K1 (12 day / without leaves of the soursop) amounted to 36.37 mg / 100 mL. The conclusion of this research is long fermentation and content of soursop leaves influence on the vitamin C activity.